2016
DOI: 10.1177/0959683616658530
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Little Ice Age’ in the Himalaya: A review of glacier advance driven by Northern Hemisphere temperature change

Abstract: Northern Hemisphere cooling between 1400 and 1900 in the Common Era (CE) resulted in the expansion of glaciers during a period known as the 'Little Ice Age' (LIA). Early investigation of recent advances of Himalayan glaciers assumed that these events were synchronous with LIA advances identified in Europe, based on the appearance and position of moraines and without numerical age control. However, applications of Quaternary dating techniques such as terrestrial cosmogenic nuclide dating have allowed researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 66 publications
(162 reference statements)
4
70
0
1
Order By: Relevance
“…However, debris‐covered and debris‐free glaciers have mostly similar trueṀ, meaning that they have to respond through different mechanisms to climate changes. The debris‐covered glaciers thin differently from the debris‐free glaciers: debris‐covered glacier thinning is distributed over their lower reaches independently of the elevation, whereas debris‐free glaciers preferentially experience front retreat (Rowan, ; Rowan et al, ; Salerno et al, ). Consequently, the ice dynamics play a major role for the evolution of debris‐covered tongues, and the stable front positions of debris‐covered glaciers should not be interpreted as balanced mass budget (Scherler et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, debris‐covered and debris‐free glaciers have mostly similar trueṀ, meaning that they have to respond through different mechanisms to climate changes. The debris‐covered glaciers thin differently from the debris‐free glaciers: debris‐covered glacier thinning is distributed over their lower reaches independently of the elevation, whereas debris‐free glaciers preferentially experience front retreat (Rowan, ; Rowan et al, ; Salerno et al, ). Consequently, the ice dynamics play a major role for the evolution of debris‐covered tongues, and the stable front positions of debris‐covered glaciers should not be interpreted as balanced mass budget (Scherler et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…M, meaning that they have to respond through different mechanisms to climate changes. The debris-covered glaciers thin differently from the debris-free glaciers: debris-covered glacier thinning is distributed over their lower reaches independently of the elevation, whereas debris-free glaciers preferentially experience front retreat (Rowan, 2017;Rowan et al, 2015;Salerno et al, 2017). Consequently, the ice…”
Section: Specificities Of Debris-covered Glaciers In Terms Of Morpholmentioning
confidence: 99%
“…This probably indicates that Neoglaciation in this part of the world was result of climatic mechanism (Monsoon) that dominates in Eastern Himalaya. The chronological records for the last millennium suggest that LIA existed here between 1300 and 1900 rather than 1300-1600 (Rowan, 2016). Spatially 30 the duration of LIA was short (between 1300 and 1600) in Eastern Himalaya (up to Everest) whereas beyond Middle Himalaya to Tian Shan the LIA records are found prolonged between 1300 and 1900 AD ( fig.6).…”
Section: Discussionmentioning
confidence: 93%
“…Recent review studies made an attempt to generate the chronological history of this area. Xu and Yi, (2014) reviewed available dates of LIA moraines in and across Tibet plateau whereas Chen et al, (2015) synthesised the proxies of moisture/precipitation in China and surrounding and Rowan, (2016) made an attempt to review the geochronological evidence for the LIA glacier advance in Himalaya. These studies reported asynchronous pattern of glacier 15 attaining their maximum extent (mostly by 1300-1600 AD) in the last millennium.…”
Section: Discussionmentioning
confidence: 99%
“…during the LGM, which corresponds to the lowering of annual temperature by 8-10°C (Kuhle 2005). Other researchers have noted the synchronous expansion of Himalayan glaciers during the Little Ice Age (Rowan 2017), suggesting overlap with the global climatic conditions. Increasing the resolution clearly requires additional data and studies.…”
mentioning
confidence: 90%